2000
DOI: 10.1038/sj.bjp.0703388
|View full text |Cite|
|
Sign up to set email alerts
|

Participation of kinins in the captopril‐induced inhibition of intimal hyperplasia caused by interruption of carotid blood flow in the mouse

Abstract: 1 In the rat balloon injury model, angiotensin-converting enzyme (ACE) inhibitors prevent vascular remodelling by inhibiting angiotensin II generation and kinin breakdown. We investigated if ACE inhibition also prevents the structural vascular responses to disruption of carotid artery blood¯ow and if kinin potentiation plays a role in such a protection. 2 Morphometric analysis of the structural alterations caused by ligation of the left carotid artery was performed 14 days after surgery in J129Sv wild-type mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…However, proangiogenic activity is not unique to ANG II. ACE inhibitors, HOE140, or the absence of the BKB2R results in reduced intimal hyperplasia produced by interrupted carotid blood flow in mice (41). These data, along with evidence that ACE inhibitors increased vessel density and capillary number in a model of surgically induced hindlimb ischemia in wild-type but not BKB2R Ϫ/Ϫ mice indicate that the BKB2R mediates the proangiogenic effect of these drugs (121).…”
Section: The Interaction Of the Plasma Kks And Ras In Angiogenesismentioning
confidence: 80%
“…However, proangiogenic activity is not unique to ANG II. ACE inhibitors, HOE140, or the absence of the BKB2R results in reduced intimal hyperplasia produced by interrupted carotid blood flow in mice (41). These data, along with evidence that ACE inhibitors increased vessel density and capillary number in a model of surgically induced hindlimb ischemia in wild-type but not BKB2R Ϫ/Ϫ mice indicate that the BKB2R mediates the proangiogenic effect of these drugs (121).…”
Section: The Interaction Of the Plasma Kks And Ras In Angiogenesismentioning
confidence: 80%
“…After the unexpected results with losartan, additional experiments were performed to clarify the mechanisms by which captopril, but not losartan, promoted collateral growth. ACEI can influence remodeling events by their effect on the kallikrein-kinin system and stimulation of NO production (15). The sulfhydryl group within captopril endows it with antioxidant properties (38) not found in most ACEI.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of intima formation in the mouse carotid after ligation showed no effect of B 1 R or B 2 R antagonists on intima. 35 In cultured VSMCs, bradykinin was shown to both stimulate 36 and inhibit growth. 23 The fact that blocking either B 1 R or B 2 R abrogated the ability of valsartan to limit intima formation is somewhat surprising, especially because blockade did not decrease AT 2 R expression.…”
Section: Discussionmentioning
confidence: 99%